Identification, Expression and Activity Analyses of Five Novel Duck Beta-Defensins - Ma, Deying; Zhang, Kexin; Zhang, Mingyue; Xin, Shengnan; Liu, Xiaoli; Han, Zongxi; Shao, Yuhao; Liu, Shengwang (PLOS ONE, 2012)
In the current study, five novel avian β-defensins (AvBDs) were identified and characterized in tissues from Peking ducks (Anas platyrhynchos). The nucleotide sequences of these cDNAs comprised 198 bp, 182 bp, 201 bp, 204 bp, and 168 bp, and encoded 65, 60, 66, 67, and 55 amino acids, respectively. Homology, characterization and comparison of these genes with AvBD from other avian species confirmed that they were Apl_AvBD1, 3, 5, 6, and 16. Recombinant AvBDs were produced and purified by expressing these genes in Escherichia coli. In addition, peptides were synthesized according to the respective AvBD sequences. Investigation of the antibacterial activity of the Apl_AvBDs showed that all of them exhibited antibacterial activity against all 12 bacteria investigated (P<0.05 or P<0.01). In addition, the antibacterial activity of all of the AvBDs against M. tetragenus and P. multocida decreased significantly in the presence of 150 mM NaCl (P<0.01). None of the AvBDs showed hemolytic activity. Consistent with their broad-spectrum antibacterial activity, the five novel Apl_AvBDs inhibited replication of duck hepatitis virus (DHV) in vitro significantly (P<0.05). The mRNA expression of all five Apl_AvBD in most tissues, including immune organs and the liver, was upregulated in response to DHV infection at different time points. These findings provide evidence that these defensins activate the immune response to combat microbial infection.